2014
DOI: 10.1002/asia.201403108
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of a DNA Triblock Copolymer that is Composed of Natural and Unnatural Nucleotides

Abstract: DNA molecules have come under the spotlight as potential templates for the fabrication of nanoscale products, such as molecular-scale electronic or photonic devices. Herein, we report an enhanced approach for the synthesis of oligoblock copolymer-type DNA by using the Klenow fragment exonuclease minus of E. coli DNA polymerase I (KF(-) ) in a multi-step reaction with natural and unnatural nucleotides. First, we confirmed the applicability of unnatural nucleotides with 7-deaza-nucleosides-which was expected bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In this study, it was found that the expression of cell proliferation related genes ( CCND1 , CCND2 , CCND3 , CDK4 , CCNB1 , CDK1 , MKI67 ) in mammary glands was not different between the CON and RFA groups, suggesting the similar status of mammary cell proliferation between groups. In support of this notion, the expression of genes ( CAD , PPAT , PSAT1 , GOT1 , GOT2 ) encoding enzymes responsible for the synthesis of nucleotides, the basic materials for DNA synthesis [ 37 ], was also not different between the CON and RFA groups. Although most metabolites concentrations in mammary vein showed similar levels between groups, intriguingly, the RFA group had higher extracellular glutamate concentration than the CON group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that the expression of cell proliferation related genes ( CCND1 , CCND2 , CCND3 , CDK4 , CCNB1 , CDK1 , MKI67 ) in mammary glands was not different between the CON and RFA groups, suggesting the similar status of mammary cell proliferation between groups. In support of this notion, the expression of genes ( CAD , PPAT , PSAT1 , GOT1 , GOT2 ) encoding enzymes responsible for the synthesis of nucleotides, the basic materials for DNA synthesis [ 37 ], was also not different between the CON and RFA groups. Although most metabolites concentrations in mammary vein showed similar levels between groups, intriguingly, the RFA group had higher extracellular glutamate concentration than the CON group.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence-specific recognition properties and chemical reactivity of nucleic acids can be easily modulated by incorporating synthetic nucleotides endowed with custom functional groups. Ijiro’s group has prepared a triblock copolymer composed of poly­(dG)/poly­(dC) parts and a poly­(7z-dG)/poly­(dC) part with sequence-selective platinum metal deposition on the GC part of the DNA block copolymers. Braun and co-workers reported sequence-specific patterning of DNA metal coating using RecA protein that prevented Ag deposition by serving as a resist .…”
Section: Metallization Of Dnamentioning
confidence: 99%
“…Previously, sequence specific metallization of poly(dG-dC) DNA was used for grafting quantum sized nanoparticle between conducting nanowires by selective polymerization and post metallization of divalent AuNP-DNA conjugates. [39][40] Also, triblock DNA copolymers comprising middle unnatural nucleo- tides and peripheral poly(dG-dC) DNA was used for creating nanojunction between the conducting wires. Although selective deposition of metals on poly(dG-dC) DNA could be effectively used for programmed assembly of conducting materials, their utilization as a bridge to connect individual DO-based templates and post-metallization is a major requirement towards potential nanoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%